Behavioural Regulation in Exercise Questionnaire in people with schizophrenia: construct validity of the Portuguese versions - Costa, R (2017)
Purpose: People with schizophrenia have low physical activity levels that can be explained by the restriction in motivation. The Behavioural Regulation in Exercise Questionnaire-2 is a 19-item scale commonly used to assess five different motivational subtypes for physical activity. However, there are limited psychometric analyses of this version in the schizophrenia context. Moreover, there is a lack of information related to the psychometric properties of version 3 of this questionnaire, with 24 items and six different motivational subtypes. The aim of this study was to examine the construct validity of both Portuguese versions in people with schizophrenia. Methods: A total of 118 persons with schizophrenia were included (30 women). Cronbach’s alpha was used for internal consistency, Pearson’s correlation for the retained motivation-types, confirmatory factor analysis for the structural validity of version 2 and exploratory factor analysis for the factor structure of version 3. Results and conclusions: Analyses of version 2 provided an adequate fit index for the structure of the five factors. Exploratory analyses suggested retaining 2 factors of version 3. The results of this study suggest that version 3 was an appropriate measure to assess controlled and autonomous motivation for physical activity in people with schizophrenia and support its use in clinical practice and research. Implications for Rehabilitation This study supports the need to identify the reasons why people with schizophrenia practice physical activity. For that purpose, it is important to use valid and cost-effective instruments. The Portuguese version of BREQ-2 confirmed a 5-factor model and showed adequate fit for the application in people with schizophrenia. However, the incremental indices values were lower than expected. The Portuguese version of BREQ-3 showed acceptable psychometric properties to assess controlled and autonomous motivation for physical activity in people with schizophrenia.